GEREJA DAN KOMUNIKASI SOSIAL - Raharjo, Stepanus Istata (STP St. Bonaventura Medan, 2019)
Communication is an essential aspect of daily human life, involving both verbal and nonverbal elements, encompassing message content and interpersonal relationships across various contexts. In the modern era, technological advancements offer new opportunities for the Catholic Church to disseminate the teachings of the Gospel through diverse communication channels. This research emphasizes the significant role of priests as faithful witnesses in the realm of digital communication, utilizing cutting-edge audiovisual technology for broader dialogue, evangelization, and catechesis, while maintaining strong spiritual roots and theological understanding. The implications of this study underscore that integrating technology into pastoral care can extend the reach and impact of religious education, enabling the faithful to better engage with and comprehend the Church's teachings within the relevant context of today's world